2003
DOI: 10.1128/jvi.77.14.7713-7719.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Inhibition of Cellular Calcium and Tyrosine Kinase Signaling Pathways Identify Targets of the HBx Protein Involved in Hepatitis B Virus Replication

Abstract: Human hepatitis B virus (HBV)HBx protein is a multifunctional protein that activates cellular signaling pathways and is thought to be essential for viral infection. Woodchuck HBV mutants that lack HBx are unable to replicate in vivo or are severely impaired. HBV replication in HepG2 cells, a human hepatoblastoma cell line, is stimulated 5-to 10-fold by HBx protein. We have utilized the HepG2, HBx-dependent HBV replication system to study the effects of activators and inhibitors of cytosolic calcium and tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 22 publications
4
110
1
Order By: Relevance
“…It seemed that mitochondrial targeting of HBx triggers at least two important signaling mediators, ROS and calcium. It was previously shown that cytoplasmic calcium released from mitochondria by HBx plays an important role in the regulation of HBV replication [21,26]. Likewise, our data here revealed that the elevated cytoplasmic calcium and subsequent activation of calcium-dependent tyrosine kinase may serve as critical cytoplasmic signals for HBx-mediated COX-2 induction.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It seemed that mitochondrial targeting of HBx triggers at least two important signaling mediators, ROS and calcium. It was previously shown that cytoplasmic calcium released from mitochondria by HBx plays an important role in the regulation of HBV replication [21,26]. Likewise, our data here revealed that the elevated cytoplasmic calcium and subsequent activation of calcium-dependent tyrosine kinase may serve as critical cytoplasmic signals for HBx-mediated COX-2 induction.…”
Section: Discussionsupporting
confidence: 79%
“…Notably, a proline-rich tyrosine kinase, Pyk2, is activated upon increased cytosolic calcium that can be released from HBx-stimulated mitochondria [21,26]. We therefore, investigated whether inhibition of Pyk2 by herbimycin or blocking mitochondrial permeability transition pore, thereby inhibiting cytosolic calcium release, using cyclosporine A (CsA), distort the HBV-mediated COX-2 induction.…”
Section: Mitochondrial Localization Of Hbx Is Necessary But Not Suffimentioning
confidence: 99%
“…Recently, in vitro experiments suggest that HBx stimulates HBV replication via its transactivation function (Melegari et al, 2005;Tang et al, 2005). It has been demonstrated that HBx action on viral replication may be dependent to modulation of calcium homeostasis, which provides novel clues for HBx biology (Bouchard et al, 2001(Bouchard et al, , 2003Choi et al, 2005). In addition, HBx interactions with the proteasome complex or DDB1 and HBx activation of Src tyrosine kinases have also been reported to participate in the regulation of HBV replication (Klein et al, 1999;Zhang et al, 2004;Leupin et al, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…The conclusion by Tang et al is clearly different from the direct role of HBx in HBV replication reported by the previous studies. (46,47) Zhang et al reported the involvement of proteasome in the stimulatory role of HBx in HBV transcription and replication. (32) Their experiments demonstrated that HBx-assisted enhancement of HBV transcription and replication is through the proteasomedependent pathway since inhibition of cellular proteasome activities enhanced HBV transcription and replication in an HBx-dependent manner.…”
Section: −10mentioning
confidence: 99%
“…(47) HBx was reported to increase the level of calcium in cells, which might be stimulatory for HBV replication because the treatment with drugs like gliotoxin and glibenclimide that augment cytoplasmic calcium ion partially rescued the HBV replication of the X-deficient replicon. They argued that the role of HBx to stimulate HBV replication is not at the level of transcription of pgRNA but at the level of DNA replication.…”
Section: −10mentioning
confidence: 99%